Chemical Composition, Antioxidant, DNA Damage Protective, Cytotoxic and Antibacterial Activities of Cyperus rotundus Rhizomes Essential Oil against Foodborne Pathogens - Hu, Qing-Ping (Sci Rep, 2017)
Cyperus rotundus L. (Cyperaceae) is a medicinal herb traditionally used to treat various clinical conditions at home. In this study, chemical composition of Cyperus rotundus rhizomes essential oil, and in vitro antioxidant, DNA damage protective and cytotoxic activities as well as antibacterial activity against foodborne pathogens were investigated. Results showed that α-cyperone (38.46%), cyperene (12.84%) and α-selinene (11.66%) were the major components of the essential oil. The essential oil had an excellent antioxidant activity, the protective effect against DNA damage, and cytotoxic effects on the human neuroblastoma SH-SY5Y cell, as well as antibacterial activity against several foodborne pathogens. These biological activities were dose-dependent, increasing with higher dosage in a certain concentration range. The antibacterial effects of essential oil were greater against Gram-positive bacteria as compared to Gram-negative bacteria, and the antibacterial effects were significantly influenced by incubation time and concentration. These results may provide biological evidence for the practical application of the C. rotundus rhizomes essential oil in food and pharmaceutical industries.